Charge‐Balancing Redox Mediators for High Color Contrast Electrochromism on Polyoxometalates. Issue 10 (30th July 2020) - Wang, Shi‐Ming; Wang, Yuhao; Wang, Tao; Han, Zhengbo; Cho, Cheolhyun; Kim, Eunkyoung
Abstract: A nonaqueous charge‐balancing electrolyte with a redox couple (I − /I3 − ) is investigated to improve the electrochromic (EC) performance of polyoxometalate (POM)‐based electrochromic devices (ECDs). PW12 O40 3− (PW12 )‐coated porous TiO2 nanoparticle films (PWTNF) with different thicknesses are used as the working electrode. The optical contrast (Δ T ) of the optimized PW12 ‐ECDs reached 59.4% with the electrolyte containing the I − /I3 − redox couple. PW12 ‐ECDs also show a fast response time for bleaching ( t b, 90% = 1.9 s) and coloration ( t c, 90% = 3.1 s). On the contrary, without the I − /I3 − redox couple, PW12 ‐ECDs show a poor Δ T of 4.0% and slow response times (>9.0 s). The role of the I − /I3 − couple is identified as a charge‐balancing redox mediator between PW12 and the counter electrode. Li + is the effective intercalating/deintercalating cation required for the EC reaction of PW12 . Thus, by simply introducing the I − /I3 − redox couple into the electrolyte significantly boosts the EC performance of POMs. Abstract : A nonaqueous charge balancing electrolyte with I − /I3 − redox couple is explored for high performance polyoxometalate based electrochromic devices (ECDs). The I − /I3 − redox couple has the functions of charge balancing and facilitates the charge transfer between polyoxometalates and counter electrode in the ECD. As a result, the optical contrast for the ECD with optimized electrolyte is enhanced significantly (15 times).